Analisis Penerapan Good Corporate Governance pada Sistem Pelaporan Keuangan BAZNAS Kabupaten Kebumen - Ambarsari, Livia; Anwar, Khoirul; Hartono, Setyo Budi; Lestari, Herwening Sindu (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2020)
The implementation of Good Corporate Governance (GCG) in the financial reporting system is an effort to encourage transparent and accountable zakat management. This study aimed to determine the financial reporting system and the application of GCG in the financial reporting system of BAZNAS Kebumen Regency. The research method in this research is qualitative with a descriptive analysis approach. The informants consisted of three informants from BAZNAS Kebumen Regency. The data used are primary data obtained through direct interviews with informants and secondary data obtained from internal institution data, financial reports and several literature studies. The results show that the financial reporting system in BAZNAS Kebumen Regency is good enough at implementing GCG in the financial reporting system with principles consisting of transparency, accountability, responsibility, independence and justice. The implementation of GCG in the financial reporting system makes BAZNAS Kebumen Regency have a transparent and accountable reporting system to increase the community's trust or muzakki to pay zakat to BAZNAS.